2012
DOI: 10.1111/j.1420-9101.2012.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

The costs of parental care: a meta‐analysis of the trade‐off between parental effort and survival in birds

Abstract: A fundamental premise of life-history theory is that organisms that increase current reproductive investment suffer increased mortality. Possibly the most studied life-history phenotypic relationship is the trade-off between parental effort and survival. However, evidence supporting this trade-off is equivocal. Here, we conducted a meta-analysis to test the generality of this tenet. Using experimental studies that manipulated parental effort in birds, we show that (i) the effect of parental effort on survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
172
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(184 citation statements)
references
References 53 publications
11
172
1
Order By: Relevance
“…This has been investigated mostly in the context of total reproductive investment, rather than per offspring investment. Also, results have been somewhat inconclusive, with no overall effect of increased reproductive investment on lifespan being found across studies in birds (Santos and Nakagawa, 2012). Although we found little evidence for genetic constraints limiting the evolution of maternal investment, there was evidence that the response to selection between the two lines was asymmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…This has been investigated mostly in the context of total reproductive investment, rather than per offspring investment. Also, results have been somewhat inconclusive, with no overall effect of increased reproductive investment on lifespan being found across studies in birds (Santos and Nakagawa, 2012). Although we found little evidence for genetic constraints limiting the evolution of maternal investment, there was evidence that the response to selection between the two lines was asymmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, clutch size is believed to be adaptive in many species and should correspond to a trade-off between the physiological constraints of producing more eggs and the energy demands during chick rearing [35]. Indeed, parental survival and future reproductive performance can be reduced due to the increased parental effort needed to rear more chicks to independence [35,36], as has been shown for great tits Parus major [37] and jackdaws Corvus monedula [38]. Our analyses revealed that food-caching birds, such as magpies, scrub-jays, shrikes, kestrels and some species of tits, increased clutch size in response to food supplementation, while non-caching species did not.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Experimental Biology (2014) conditions, experimental brood enlargements in wild birds may result in parents being able to raise all the nestlings without incurring any costs in terms of reduced survival or future breeding performance (Dijkstra et al, 1990;Santos and Nakagawa, 2012). Studies on wild birds or mammals have also found that individuals reproducing in high quality environments had lower oxidative stress than those reproducing under poorer environmental conditions.…”
Section: Research Articlementioning
confidence: 99%
“…van de Crommenacker et al, 2011;Fletcher et al, 2013)] and investigated whether higher effort induces an increase in blood oxidative damage, an increase in ceruloplasmin activity in plasma and a reduction in the non-protein and protein thiols. To this end, we enlarged or reduced the brood size, which is a relatively easy way of altering parental effort in altricial avian species (Dijkstra et al, 1990;Santos and Nakagawa, 2012). We also compared the blood oxidative stress level of reproducing birds with that of non-reproducing birds.…”
Section: Introductionmentioning
confidence: 99%